Evaluating the taxonomic status of Solanum nigrum L. using flow cytometry and DNA barcoding technique - P Paramaguru, T Nandhini, (Journal of Spices and Aromatic Crops, 2014)
Solanum nigrum L. is a widely distributed species whose taxonomic status remains controversial. The ploidy determination of all the accessions were done based on stomatal, pollen and some morphological characters but morphometry could not provide solution to distinguish these species. In this study, ploidy status of all the accessions were done using flow cytometry and DNA barcoding technique was also applied to identify and distinguish 13 distinct germplasm collections. DNA of all 13 accessions was isolated and sequenced. The sequence was aligned using DNASTAR offline Software. The DNA sequence was subjected to BLAST for identifying at species level. The intra specific variation between the species was calculated using MEGA 5.0. The phylogenetic analysis indicated that among the 13 accessions, six were identified as S. americanum Mill, three were identified as S. nigrum Linn. and four were identified as S. villosum Mill.